Profitabilitas, Solvabilitas dan Likuiditas terhadap Nilai Perusahaan - Salsabila Rizki Saputri; Gendro Wiyono; Ratih Kusumawardhani (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
A manufacturing company is a company whose main activity is to obtain goods and services to be processed into finished products through the production process of efficacy sold to customers. Food and beverage companies are one of the categories of the industrial sector on the Indonesia Stock Exchange (IDX) that have the opportunity to grow and develop. The development of this industry can be seen from the growth and development of companies engaged in the food and beverage industry. This study was conducted to determine the effect of Solvency, Profitability, and Liquidity on Food and Beverage Companies listed on the Indonesia Stock Exchange on the Indonesia Stock Exchange for the 2015-2020 period. The nature of the research in this study is quantitative research and the data used are secondary to Profitability, Solvency, Liquidity as independent variables and Company Value as Dependent variables. The object of this study is a manufacturing company listed on the Indonesia Stock Exchange for the 2015-2020 period. In this study, the data used in the annual report of manufacturing companies listed on the Indonesia Stock Exchange (IDX) 2015-2020. The population in this study is all food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique used in this study used purposive sampling. The data collection method used by the author is to use the data collection method with internet research, namely the collection of indirect observation data by collecting data on annual financial statements, an overview and development of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2015-2020 period by accessing directly to the address of the www.idx.co.id. Data analysis was carried out by classical assumption testing and for hypothesis testing by multiple linear regression methods. The results of this study show that the profitability ratio measured using Return On Assets (ROA) has a positive and significant effect on company value, solvency ratios measured using Debt Ratio have a positive and significant effect on company value, Liquidity ratios measured using Cash Ratio have a positive and significant effect on company value, Profitability, solvency and liquidity ratios simultaneously have an effect positive and significant to the value of the company Keywords: Profitability, Solvency, Liquidity, Value Of The Company